PERTUMBUHAN MINI MARKET SEBAGAI SALAH SATU BENTUK PASAR MODERN - Yenli Megawati (Universitas Bunda Mulia, 2017)
The concept of Store Environment have become something of a trend around 1990 until now especially since economic crisis and interest rates on deposit accounts are not so attractive anymore besides shifting in consumer habits. The growth of mini markets as a business that adopts this concept has become really high in many parts of the world especially in Indonesia. The growth of mini markets have negative impact on local business or traditional markets but on the other hand, it also has positive impacts on job opportunities for community. Keywords: modern market, mini markets, franchises, traditional market